2007
DOI: 10.1016/j.trstmh.2007.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Malaria risk perception, knowledge and prophylaxis practices among travellers of African ethnicity living in Paris and visiting their country of origin in sub-Saharan Africa

Abstract: An observational prospective cohort study assessed malaria risk perception, knowledge and prophylaxis practices among individuals of African ethnicity living in Paris and travelling to their country of origin to visit friends or relatives (VFR). The study compared two groups of VFR who had visited a travel clinic (TC; n=122) or a travel agency (TA; n=69) before departure. Of the 47% of VFR citing malaria as a health concern, 75% knew that malaria is mosquito-borne and that bed nets are an effective preventive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
10

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 11 publications
3
61
0
10
Order By: Relevance
“…21,22 VFR travelers in our study were not less adherent to chemoprophylaxis compared with others; however, previous research has shown that VFR travelers who attend a pre-travel health consultation at a travel health clinic adhere more to chemoprophylaxis than those who do not attend a consultation. 23 Therefore, VFRs in our study may not be representative of all VFR travelers. Participants may have underreported how many pills were missed.…”
Section: Discussionmentioning
confidence: 92%
“…21,22 VFR travelers in our study were not less adherent to chemoprophylaxis compared with others; however, previous research has shown that VFR travelers who attend a pre-travel health consultation at a travel health clinic adhere more to chemoprophylaxis than those who do not attend a consultation. 23 Therefore, VFRs in our study may not be representative of all VFR travelers. Participants may have underreported how many pills were missed.…”
Section: Discussionmentioning
confidence: 92%
“…La CQ seule a été cinq fois moins utilisée en CPAP par les patients de Bordeaux qu'au niveau national, probablement en raison d'une sous-représentation des VFR à Bordeaux. Les VFR semblent effectivement avoir une plus grande propension à recourir à une CPAP par CQ, vraisemblablement en raison de son faible coût et de sa popularité malheureusement encore grande en Afrique subsaharienne, à Madagascar et aux Comores [21,22]. La prépondérance du recours à CP chez les patients pourrait être liée à l'association de plusieurs facteurs.…”
Section: Discussionunclassified
“…Cette différence notable pourrait être liée à un biais de sous-déclaration du recours à la moustiquaire à l'échelle nationale. Une autre explication plausible de cette différence serait que les patients de notre série, majoritairement des « non-VFR », pourraient avoir une perception des risques liés aux piqûres de moustiques globalement plus élevée que les patients recensés par le CNRP, ces derniers étant majoritairement des VFR croyant à l'hypothé-tique pérennité de leur semi-immunité palustre et annonçant à tort, l'inutilité de la prévention [1,14,16,18,20,21,25]. Ces croyances erronées peuvent même parfois influencer les médecins prescripteurs de mesures préventives [4].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Approximately 40-50% [9][10][11] of the travellers to Africa are ethnic Africans living in industrialized countries visiting friends and relatives (VFR) to their home countries. VFR often belong to a social class with limited income, especially in France [12] and so have low recourse to MC [8,13].…”
Section: Introductionmentioning
confidence: 99%